Financing MNC Subsidiaries in Central America - Errunza, Vihang R. (Journal of International Business Studies, 1979)
This articles studies the historical financial sources for MNC activity in Costa Rica, Honduras, and Nicaragua. The evidence suggests that country environment factors have dominated the sourcing policies of MNCs. The most important factors include perceived exchange risk and domestic credit conditions.